alexandria/documents/by-course/math-8/pset-5/main.typ

716 lines
20 KiB
Text
Raw Blame History

This file contains ambiguous Unicode characters

This file contains Unicode characters that might be confused with other characters. If you think that this is intentional, you can safely ignore this warning. Use the Escape button to reveal them.

#import "@youwen/zen:0.1.0": *
#import "@preview/mitex:0.2.5": *
#show: zen.with(
title: "Homework 5",
author: "Youwen Wu",
)
#set heading(numbering: none)
#show heading.where(level: 2): it => [#it.body.]
#show heading.where(level: 3): it => [#it.body.]
#set par(spacing: 1em)
Problems:
2.4: \#4bcde, 5ajq, 6ce, 7a, 9, 10, 12abc
2.5: \#1abc, 3, 10
= 2.4
== 4
=== b
$3 + 11 + 19 + dots.c + (8n - 5) = 4n^2 - n$
#proof[
First we show the base case for $n = 1$.
$ 3 = 4 (1^2) - 1 = 3 $
Now we proceed by induction. Assume $sum _(k=1) ^n (8k-5) = 4(n^2) - n$.
$
sum_(k=1)^(n+1) (8k-5) &= 4((n+1)^2) - (n+1) \
(sum_(k=1)^(n) (8k-5)) + (8(n+1) - 5) &= 4(n^2 + 2n + 1) - n-1 \
(sum_(k=1)^(n) (8k-5)) + 8n + 3 &= 4n^2 - n + 8n + 3 \
(sum_(k=1)^(n) (8k-5)) &= 4n^2 - n \
$
and we know that this is true by our original assumption. So by the PMI, this
is true $forall n in NN$.
]
=== c
#proof[
$sum_(i=1)^n 2^i = 2^(n+1) - 2$
For the base case:
$ 2^1 = 2(1 + 1) - 2 \ 2 = 2 $
Assume that
$
sum_(i=1)^n 2^i = 2^(n+1) - 2
$
Proceeding by induction,
$
sum_(i=1)^(n+1) 2^i = 2^(n+1+1) - 2 \
(sum_(i=1)^(n) 2^i) + 2^(n+1) = 2^(n+2) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+2) - 2^(n+1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) dot (2 - 1) - 2 \
(sum_(i=1)^(n) 2^i) = 2^(n+1) - 2 \
$
So by the PMI, it holds for all $n in NN$.
]
=== d
#proof[
$1 dot 1! + 2 dot 2! + 3 dot 3! + dots.c + n dot n! = (n + 1)! - 1$
For the base case: $1 dot 1! = (1 + 1)! - 1 \ 1 = 1$
Assuming the inductive hypothesis,
$
sum^n_(k=1) k dot k! = (n + 1)! - 1 \
$
Now we proceed by induction
$
sum^(n+1)_(k=1) k dot k! = (n + 2)! - 1 \
sum^(n)_(k=1) k dot k! + (n + 1) dot (n+1)! = (n + 2) dot (n + 1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 2) dot (n + 1)! - (n + 1) dot (n+1)! - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! dot (n+2 - (n + 1) - 1 \
sum^(n)_(k=1) k dot k! = (n + 1)! - 1 \
$
So by the PMI, this is true for all $n in NN$.
]
=== e
#proof[
$1^3 + 2^3 + dots.c + n^3 = [(n(n+1)) / 2]^2$
First checking the base case:
$
1^3 = [(1(1 + 1)) / 2]^2 \
1 = 1
$
Now assume the inductive hypothesis
$ sum_(k=1)^n k^3 = [(n(n+1)) / 2]^2 $
Proceeding by induction,
$
sum_(k=1)^(n + 1) k^3 = [((n+1)(n+2)) / 2]^2 \
sum_(k=1)^(n) k^3 + (n+1)^3 = ((n+1)^2 (n+2)^2) / 4 \
sum_(k=1)^(n) k^3 = ((n+1)^2 (n+2)^2) / 4 - (n+1)^3 \
sum_(k=1)^(n) k^3 = ((n+1)^2 [(n+2)^2 - 4(n+1)]) / 4 \
sum_(k=1)^(n) k^3 = ((n+1)^2 n^2) / 4 \
sum_(k=1)^(n) k^3 = [(n (n+1)) / 2]^2 \
$
So by the PMI it is true $forall n in NN$.
]
== 5
=== a
$n^3 + 5n + 6$ is divisible by 3.
#proof[
Checking the base case,
$
3 | 1^3 + 5(1) + 6 \
3 | 12
$
Now assume the inductive hypothesis.
$
3 | n^3 + 5n + 6
$
Proceeding by induction,
$
3 | (n+1)^3 + 5(n+1) + 6 \
3 | (n+1)^3 + 5(n+1) + 6 \
3 | n^3 + 3n^2 + 3n + 1 + 5n + 5 + 6 \
3 | n^3 + 5n + 6 + 3n^2 + 3n + 6 \
$
By our inductive hypothesis, we know that $3 | n^3 + 5n + 6$. Additionally we
clearly see that $3 | 3n^2 + 3n + 6$ as it can be factored out. So the
$(n+1)^"th"$ case is true and by the PMI, it is true for all $n in NN$.
]
=== j
$3^n >= 1 + 2^n$
#proof[
Base case: $ 3^1 >= 1 + 2^1 \ 3 >= 3 $
Assume the inductive hypothesis
$
3^n >= 1 + 2^n
$
Now proceed by induction
$
3^(n+1) >= 1 + 2^(n+1)
$
We want to show that this statement is always true. Rewrite the left side as
$3 dot 3^n$, then we can derive the following inequality from our inductive
hypothesis:
$
3 dot 3^n >= 3(1 + 2^n) \
3 dot 3^n >= (2 + 1)(1 + 2^n) \
3 dot 3^n >= 2 + 2^(n+1) + 1 + 2^n \
$
And clearly we have
$
2 + 2^(n+1) + 1 + 2^n >= 1 + 2^(n+1)
$
So,
$
3^(n+1) >= 1 + 2^(n+1) + 2 + 2^n >= 1 + 2^(n+1)
$
We have shown that it applies to the $(n+1)^"th"$ case when the $n^"th"$ is
true. Therefore by the PMI it is true $forall n in NN$.
]
=== q
If a set $A$ has $n$ elements, then $cal(P) (A)$ has $2^n$ elements.
#proof[
Just for fun, consider an $n$-tuple that encodes a subset of $A$. Each entry
corresponds to a different element in $A$, and is 1 if that element is in the
subset, and 0 if it is not. Now to count the cardinality of $cal(P)(A)$, we
simply need to count each possible combination of entries in our tuple, as
each tuple corresponds to a unique subset of $A$. Since there are 2
alternatives for each entry and $n$ entries, by the general multiplication
principle, there are $2^n$ variants of this tuple so the cardinality of
$cal(P)(A)$ is $2^n$.
---
Ok now let's do it the annoying way.
Consider the set with $0$ elements, $X = {}$. Then $cal(P)(X) = {emptyset}$
so indeed it has cardinality $2^0 = 1$. Otherwise suppose that any set $X$
with $n$ elements indeed has $|cal(P)(X)| = 2^n$.
Then, consider a set $Y$ of $n+1$ elements. For each subset of $cal(P)(Y)$,
we choose an arbitrary element $k in Y$, and define $Z := Y backslash {k}$.
Note that $Z$ has $n$ elements so our inductive hypothesis says it has $2^n$
elements. We seek to show that this implies $cal(P)(Y)$ has $2^(n+1)$
elements.
Every subset of $Y$ in $cal(P)(Y)$ satisfies the following: either the subset
does not contain $k$ and so it's also a subset of $Z$, or its only difference
from a subset of $Z$ is the addition of $k$.
Therefore, for each subset of $Z$, we can introduce $k$, and it's still a
subset of $Y$, and in fact completes $cal(P)(Y)$ from $cal(P)(Z)$, due to our
previous assertion. So for each element in $cal(P)(Z)$, there is one
additional element in $cal(P)(Y)$. In other words,
$
|cal(P)(Z)| dot 2 = |cal(P)(Y)|
$
Recall our inductive hypothesis states $|cal(P)(Z)| = 2^n$ because $Z$ has
$n$ elements, so $|cal(P)(X)| = 2 dot |cal(P)(Z)| = 2^(n+1)$, completing our
induction. Therefore for any arbitrary set $X$ with $n$ elements, its power
set $cal(P)(X)$ has $2^n$ elements.
// #mitext(`
// Base Case ($n=0$). \\
// If $A$ has $0$ elements, then $A = \varnothing$. Its power set is
// \[
// \mathcal{P}(A) = \{\varnothing\},
// \]
// which has exactly one element. Hence
// \[
// |\mathcal{P}(A)| = 1 = 2^0.
// \]
// So the statement holds for $n=0$.
//
// Now proceed by induction. Assume the statement is true for some integer $k \ge
// 0$. That is, suppose that for any set $A$ with $k$ elements, we have
// \[
// |\mathcal{P}(A)| = 2^k.
// \]
//
// Let $B$ be a set with $k+1$ elements. Choose one element $x \in B$, and let $A = B \setminus \{x\}$. Then $A$ has $k$ elements. By the inductive hypothesis,
// \[
// |\mathcal{P}(A)| = 2^k.
// \]
// Now observe that any subset of $B$ is either:
// \begin{itemize}
// \item A subset of $A$ (does not contain $x$), or
// \item Of the form $S \cup \{x\}$ where $S \subseteq A$ (does contain $x$).
// \end{itemize}
// Thus every subset of $A$ gives rise to exactly one subset of $B$ that excludes $x$, and exactly one subset of $B$ that includes $x$. Therefore,
// \[
// |\mathcal{P}(B)| = |\mathcal{P}(A)| + |\mathcal{P}(A)|
// = 2^k + 2^k
// = 2 \cdot 2^k
// = 2^{k+1}.
// \]
//
// Since $B$ was any set with $k+1$ elements, the statement holds for $k+1$. By the principle of mathematical induction, the proof is complete.
// `)
]
== 6
=== c
$(n+1)! > 2^(n+3)$ for all $n >= 5$.
Consider $n = 5$. Then $6! > 2^(8)$. Now proceed by induction. Suppose that
$(n+1)! > 2^(n + 3)$.
Then $(n + 1 + 1)! > 2^(n+3 + 1)$ so $(n + 2)(n+1)! > 2 dot 2^(n + 3)$. We note
that $n+2$ is always at least $2$, so this is true by our inductive hypothesis.
If we consider $n = 1$, then $2! < 2^(4)$ so the PMI does not hold for all $NN$.
// #mitext(`
// Let \( n = 5 \). Then:
// \[
// (5+1)! = 6! = 720 \quad\text{and}\quad 2^{5+3} = 2^8 = 256.
// \]
// Since \( 720 > 256 \), the inequality holds for \( n = 5 \).
//
// Assume that for some natural number \( n \ge 5 \) the inequality holds for all integers \( m \) with \( 5 \le m \le n \). In particular, assume
// \[
// (n+1)! > 2^{n+3}.
// \]
// We must show that
// \[
// (n+2)! > 2^{(n+1)+3} = 2^{n+4}.
// \]
//
// Starting with the left-hand side, we have:
// \[
// (n+2)! = (n+2)(n+1)!.
// \]
// Using the inductive hypothesis,
// \[
// (n+2)! > (n+2) \cdot 2^{n+3}.
// \]
// Since \( n \ge 5 \), it follows that \( n+2 \ge 7 \). Therefore,
// \[
// (n+2) \cdot 2^{n+3} \ge 7 \cdot 2^{n+3}.
// \]
// But clearly,
// \[
// 7 \cdot 2^{n+3} > 2 \cdot 2^{n+3} = 2^{n+4}.
// \]
// Thus,
// \[
// (n+2)! > 2^{n+4},
// \]
// which completes the inductive step.
//
// By the generalized principle of mathematical induction, the inequality
// \[
// (n+1)! > 2^{n+3}
// \]
// holds for all natural numbers \( n \ge 5 \).
//
// The inequality is stated to hold for all \( n \ge 5 \). However, for \( n < 5 \) the inequality fails. For instance, when \( n = 4 \):
// \[
// (4+1)! = 5! = 120 \quad\text{and}\quad 2^{4+3} = 2^7 = 128.
// \]
// Since \( 120 \) is not greater than \( 128 \), the inequality is false for \( n = 4 \).
// `)
=== e
$(n! > 3n)$ for all $n >= 4$.
Consider $n = 4$. Then $4! > 3(4)$. Suppose $(n! > 3n)$. Then
$
(n+1)! > 3(n+1) \
(n+1)n! > 3n + 3
$
Assume $n >= 4$. Then the above statement holds true for any $n$. So we
conclude the statement is always true for $n >= 4$.
// #mitext(`
// Let \( n = 4 \). Then:
// \[
// 4! = 24 \quad\text{and}\quad 3 \times 4 = 12.
// \]
// Since \( 24 > 12 \), the inequality holds for \( n = 4 \).
//
// Assume that for some natural number \( n \ge 4 \) the inequality holds for all integers \( m \) with \( 4 \le m \le n \). In particular, assume that
// \[
// n! > 3n.
// \]
// We must show that
// \[
// (n+1)! > 3(n+1).
// \]
//
// Starting with the left-hand side:
// \[
// (n+1)! = (n+1) \cdot n!.
// \]
// By the inductive hypothesis, we have:
// \[
// (n+1)! > (n+1) \cdot 3n.
// \]
// Since \( n \ge 4 \) (so \( n \ge 2 \)), it follows that:
// \[
// (n+1) \cdot 3n \ge 3(n+1).
// \]
// To see this, note that for \( n \ge 2 \) we have:
// \[
// 3n(n+1) = 3(n+1)n > 3(n+1),
// \]
// because \( n > 1 \). Therefore,
// \[
// (n+1)! > 3(n+1),
// \]
// which completes the inductive step.
//
// By the generalized principle of mathematical induction, the inequality
// \[
// n! > 3n
// \]
// holds for all natural numbers \( n \ge 4 \).
//
// The claim is that \( n! > 3n \) for all \( n \ge 4 \). However, for some smaller natural numbers the inequality is false. For instance, when \( n = 3 \):
// \[
// 3! = 6 \quad\text{and}\quad 3 \times 3 = 9.
// \]
// `)
== 7
=== a
$
(sect.big^n_(i=1) A_i)^c = union.big^n_(i=1) A_i^c
$
First consider $sect.big^n_(i=1) A_i$. Let $X := sect.big^n_(i=1) A_i$.
Then $x in X$ if and only if $x in A_i$ for every $A_i$.
Now consider $Y := (sect.big^n_(i=1) A_i)^c$. Then $y in Y$ if and only if $y
in.not X$, that is, if and only there exists some $A_i$ such that $y in.not
A_i$. Now let $Z := union.big^n_(i=1) A_i^c$. Every element $z in Z$ is in some
$A^c _i$, that is, $z in Z$ if and only if there exists some $A_i$ such that $z
in.not A_i$. Now note this is actually precisely the definition of $Y$. Hence
$Z = Y$.
// #mitext(`
// Let \(\{A_i : i \in \mathbb{N}\}\) be an indexed family of sets. Then for every natural number \( n\ge1 \),
// \[
// \left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c
// \]
// and
// \[
// \left(\bigcap_{i=1}^{n} A_i\right)^c = \bigcup_{i=1}^{n} A_i^c.
// \]
//
// For \( n=1 \), we have
// \[
// \left(\bigcup_{i=1}^{1} A_i\right)^c = A_1^c \quad \text{and} \quad \bigcap_{i=1}^{1} A_i^c = A_1^c.
// \]
// Thus, the identity holds for \( n=1 \).
//
// Assume that for some \( n \ge 1 \) the statement holds; that is, assume
// \[
// \left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
// \]
// We need to show that
// \[
// \left(\bigcup_{i=1}^{n+1} A_i\right)^c = \bigcap_{i=1}^{n+1} A_i^c.
// \]
//
// Notice that
// \[
// \bigcup_{i=1}^{n+1} A_i = \left(\bigcup_{i=1}^{n} A_i\right) \cup A_{n+1}.
// \]
// Taking the complement of both sides, and using De Morgan's Law for two sets, we obtain:
// \[
// \left(\bigcup_{i=1}^{n+1} A_i\right)^c = \left(\left(\bigcup_{i=1}^{n} A_i\right) \cup A_{n+1}\right)^c = \left(\bigcup_{i=1}^{n} A_i\right)^c \cap A_{n+1}^c.
// \]
// By the induction hypothesis,
// \[
// \left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
// \]
// Thus, we have:
// \[
// \left(\bigcup_{i=1}^{n+1} A_i\right)^c = \left(\bigcap_{i=1}^{n} A_i^c\right) \cap A_{n+1}^c = \bigcap_{i=1}^{n+1} A_i^c.
// \]
//
// This completes the inductive step.
//
// By the PMI, we conclude that for every natural number \( n\ge1 \),
// \[
// \left(\bigcup_{i=1}^{n} A_i\right)^c = \bigcap_{i=1}^{n} A_i^c.
// \]
//
// Thus, De Morgan's Laws hold for any indexed family \(\{A_i : i \in \mathbb{N}\}\).
// `)
== 9
Suppose there was one point. Then there would be $(1^2 - 1)/2 = 0$ line
segments which is correct. Now we proceed by induction. Suppose that for
$n$ points, the number of line segments joining all pairs of points are $(n^2 -
n)/2$. Now introduce an additional point such that there are $n+1$ points. For
each of the previous $n$ points, we draw a line connecting it to the newly
added point. So we introduce $n$ additional lines. Therefore we have
$
(n^2 - n) / 2 + n
$
lines, which we can rewrite
$
(n^2 + n) / 2 = ((n+1)^2 - (n+1)) / 2
$
So we conclude that our hypothesis holds for $n+1$ points and therefore holds
for all $n in NN$ points.
// #mitext(`
// Given \(n\) points \(P_1, P_2, \dots, P_n\) in a plane with no three collinear, the number of line segments joining every pair of points is
// \[
// \frac{n^2 - n}{2}.
// \]
//
// For \(n=2\), there is exactly 1 line segment joining the two points. The formula gives
// \[
// \frac{2^2 - 2}{2} = \frac{4-2}{2} = 1.
// \]
// So the statement holds for \(n=2\).
//
// Assume that for some \(n \ge 2\), the number of line segments joining \(n\) points is
// \[
// \frac{n^2 - n}{2}.
// \]
// Now consider \(n+1\) points. When we add a new point \(P_{n+1}\), this new point can be connected to each of the \(n\) existing points, thereby adding \(n\) new segments. Hence, the total number of segments becomes
// \[
// \frac{n^2 - n}{2} + n.
// \]
// Simplify the expression:
// \[
// \frac{n^2 - n}{2} + n = \frac{n^2 - n + 2n}{2} = \frac{n^2 + n}{2} = \frac{n(n+1)}{2}.
// \]
// Therefore, by the PMI, the number of line segments joining all pairs of \(n\) points is
// \[
// \frac{n^2 - n}{2}
// \]
// for all \(n \ge 2\).
// `)
== 10
First, note that with 1 disk, it takes $2^1 - 1 = 1$ moves to solve the puzzle.
Now suppose that for $n$ disks, it takes $2^n - 1$ moves to solve. We proceed
by induction on $n+1$ disks. First, ignore the disk at the very bottom of the
stack, such that our situation is equivalent to when there are $n$ disks
(because any disk can be stacked on top of the largest disk, our set of
possible moves is unchanged from $n$ disks). Then we can move each of these
disks to another peg in $2^n - 1$ moves. Now move the largest disk, which now
no more disks above it, to the other free peg. Now we again can ignore the
largest disk and move our $n$ disks on top of the largest disk in $2^n - 1$
moves. So it took us a total of $2 dot (2^n - 1) + 1$ moves to move the entire
stack to another peg, or $2^(n+1) - 1$ moves.
== 12
=== a
F.
The inductive step assumes that two overlapping sets of $n$ horses share at
least $n1$ horses in common, so that they must all be the same color. But
when $n=1$, two different 1horse sets do not overlap at all, so the argument
that “both sets share a horse of the same color” no longer applies.
=== b
F.
The inductive step is not shown, so there is no justification for the claim
that it is divisible.
=== c
C.
Though the inductive reasoning is right, the base case is not shown, so there
is no reason why this should hold true for all $NN$.
= 2.5
== 1
=== a
Every natural number greater than or equal to 11 can be written in the form $2s
+ 5t$ for some naturals $s$ and $t$.
First, we see that $11 = 2(3) + 5(1)$, $12 = 2(2) + 5(2)$, $13 = 2(4) + 5(1)$,
$14 = 2(2) + 5(2)$. Now suppose that we can write all naturals up to $11 <= k
<= n$ as $2s + 5t$ for naturals $s,t$. Note that we have shown naturals from 11
to 15 can be written in the $2s + 5t$ form. Then we note $n >= 15$ iff. $n - 4 >= 11$,
and $n - 4$ is covered
by our inductive hypothesis, so we can write
$
n + 1 = (n - 4) + 4 + 1 = 2s + 5t + 5 = 2s + 5(t + 1)
$
So indeed $n+1$ can be written as $2s + 5t$ for some naturals $s, t$.
=== b
#mitext(`
Every natural number \( n > 22 \) (i.e. every \( n \ge 23 \)) can be written in the form
\[
n = 3s + 4t,
\]
with integers \( s \ge 3 \) and \( t \ge 2 \).
`)
#proof[
First, let's consider a few base cases.
$
23 &= 3(5) + 4(2) \
24 &= 3(4) + 4(3) \
25 &= 3(3) + 4(4) \
$
So for 23, 24, and 25, we can write them in the form $3s + 4t$ such that $s
>= 3$ and $t >= 2$. Now we proceed by strong
induction. Suppose that any natural $23 <= k <= n$ can be written as $k = 3s
+ 4t$ for $t >= 2$ and $s >= 3$. Note that when $n >= 26$, $n - 3 >= 23$
(otherwise, it's already covered in our base case and we are done). Then we
can assume $n-3$ is always covered by the inductive hypothesis and can be
written in the desired form $3s + 4t$. Now we seek to show that this implies
$n+1$ can also be written in this form.
$
(n+1) = (n-3) + 4 = 3s + 4t + 4 = 3s + 4(t+1)
$
And $s >= 3$, $t + 1 >= 2$. So indeed any natural number greater than 22 can
be written as $3s + 4t$ for some naturals $t >= 2$ and $s >= 3$.
]
=== c
#mitext(`
Every natural number \( n > 33 \) (i.e. every \( n \ge 34 \)) can be written in the form
\[
n = 4s + 5t,
\]
where \( s \) and \( t \) are integers with \( s \ge 3 \) and \( t \ge 2 \).
`)
#proof[
We seek to show the proposition. We first show a few base cases, for $n = 34,
35, 36$.
$
34 &= 4(6) + 5(2) \
35 &= 4(5) + 5(3) \
36 &= 4(4) + 5(4)
$
Now we state our inductive hypothesis. Suppose that for some natural $n$, $34
<= k <= n$ can be written in the form $k = 4s + 5t$, for some integral $s >=
3$ and $t >= 2$. Then we proceed by strong induction. Note that if $n >= 37$,
then $n - 3 >= 34$ so $n - 3$ is covered by our inductive hypothesis
(otherwise $n$ would be covered by one of our base cases and we are done). So
$n-3$ can be written in the desired $4s + 5t$ form. Now we seek to show that
this implies $n+1$ can also be written in the desired form.
$
n + 1 = (n - 3) + 4 = 4s + 5t + 4 = 4(s+1) + 5t
$
$s+1 >= 3$ because $s >= 3$ and $t >= 2$ is still true. So indeed $n+1$ can
be written in the desired form. By strong induction, every natural $n >= 34$
can be written as $n = 4s + 5t$ for some integral $s >= 3$ and $t >= 2$.
]
== 3
#mitext(`
Let the sequence \(\{a_n\}\) be defined by
\[
a_1 = 2,\quad a_2 = 4,\quad a_{n+2} = 5a_{n+1} - 6a_n \quad \text{for all } n \ge 1.
\]
Then for all natural numbers \( n \),
\[
a_n = 2^n.
\]
`)
#proof[
We already have bases cases for $n = 1$ and $n = 2$, so we just need to show
assume the inductive hypothesis for $n > 2$. Note that when $n > 2$,
$a_(n+1)$
is
$
a_(n+1) = 5a_(n) - 6a_(n-1)
$
Suppose that all $a_k$ such that $3 <= k <= n$ are given by $a_k = 2^k$. We
seek to show that $n+1$ is also given by this equation.
Because $a_n$ and $a_(n-1)$ are included in our inductive hypothesis,
we have
$
a_(n+1) = 5(2^n) - 6(2^(n-1) = 5(2^n) - 3(2^n) = 2^(n+1)
$
Therefore indeed $a_(n+1)$ is given by $2^(n+1)$ which satisfies our
proposition and so it is true for all natural numbers.
]
== 10
#mitext(`
Every nonempty subset \( S \) of \(\mathbb{Z}^-\) (the set of negative integers) has a largest element.
`)
#proof[
We construct a new set, $S' = {-x | x in S}$. Then we note that $S'$ is a set
of positive integers, and in fact $S' subset.eq NN$. By the well ordering
principle, $S'$ always has a least element. Call this least element $k in
S'$. $k$ is the least element in $S'$ if and only if $-k$ is the greatest
element in $S$. Thus, $S$ always has a largest element.
]